Prospek Kajian Hadis di Peguruan Tinggi Keagamaan Islam di Indonesia - Suryadilaga, Muhammad Alfatih (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
Along with the development of the era of the study of hadith today, it is increasingly interesting and has good prospects because of the special institutional development in universities, where currently the hadith science study program is separate from the interpretation study program. The realm of hadith study studies is also growing well, where in its history it has produced studies on the science of hadith and certain hadith books. At present the study of hadith science not only examines the region but it also develops into the realm of studies which contextualize and understand in a society known as living hadith. In addition, technological developments make the study of hadith easily accessible to the public, so that they can carry out the teachings brought by the Prophet Muhammad. In addition, the development of the study of hadith correlated with the media is quite popular today, where the reviewers of hadith no longer dwell on the academic dimension, but they penetrate the use of social media in disseminating the results of the hadith studies conducted.